Cluster partition-based two-layer expansion planning of grid–resource–storage for distribution networks - Yang, Song; Wang, Chenglong; Sun, Shumin; Cheng, Yan; Yu, Peng (Frontiers in Energy Research, 2024)
In order to realize the optimal planning of grid-source-storage for distribution networks (DN) with high penetrated distributed photovoltaics (PV), a cluster partition based two-layer expansion planning for DNs is proposed. Firstly, a comprehensive cluster partition index based cluster partition method is proposed, which involves the indexs such as electrical distance, power balance of cluster and cluster size. Secondly, a cluster partition based two-layer expansion planning model is proposed. In the upper layer, a line planning model for clusters is established to carry out the planning of cluster connection lines. In the lower layer, a robust source-storage planning model is established with the uncertainty of PVs and loads, then the optimal location and capacity of PVs and energy storages (ES) can be obtained. And the uncertainty regulation parameter is utilized to controlling the range of uncertainty sets, which can reduce the conservatism of the optimization. Finally, the proposed method is carried out in a real DN in China, which can effectively improve the economy of DN planning.